2010
DOI: 10.1007/s00299-010-0979-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene identification in black cohosh (Actaea racemosa L.): expressed sequence tag profiling and genetic screening yields candidate genes for production of bioactive secondary metabolites

Abstract: Black cohosh (Actaea racemosa L., syn. Cimicifuga racemosa, Nutt., Ranunculaceae) is a popular herb used for relieving menopausal discomforts. A variety of secondary metabolites, including triterpenoids, phenolic dimers, and serotonin derivatives have been associated with its biological activity, but the genes and metabolic pathways as well as the tissue distribution of their production in this plant are unknown. A gene discovery effort was initiated in A. racemosa by partial sequencing of cDNA libraries const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…NMS demonstrates an affinity for serotonin receptors 5-HT1A and 5-HT7, providing a possible mechanism by which black cohosh ameliorates hot flashes (Burdette et al, 2003;Hedlund and Sutcliffe, 2004;Powell et al, 2008). Interestingly, NMS is present in black cohosh in micromolar concentrations and genetic analysis of the plant revealed that expression of genes encoding for enzymes instrumental in serotonin biosynthesis is negligible and inconsistent (Spiering et al, 2011).…”
Section: Phytochemistry: Efficacy and Toxicitymentioning
confidence: 97%
“…NMS demonstrates an affinity for serotonin receptors 5-HT1A and 5-HT7, providing a possible mechanism by which black cohosh ameliorates hot flashes (Burdette et al, 2003;Hedlund and Sutcliffe, 2004;Powell et al, 2008). Interestingly, NMS is present in black cohosh in micromolar concentrations and genetic analysis of the plant revealed that expression of genes encoding for enzymes instrumental in serotonin biosynthesis is negligible and inconsistent (Spiering et al, 2011).…”
Section: Phytochemistry: Efficacy and Toxicitymentioning
confidence: 97%
“…The approach appears independent of genotype, and relies on temperature stratification to overcome the low yields of plants due to double dormancy. This method has been used to generate a robust collection of seedlings for transplantation with a high survival rate, and for use as young plant material in studies aimed at developing cell culture, transformation and functional genomics approaches to study gene-metabolite relationships in this important non-model medicinal plant [21].…”
Section: Discussionmentioning
confidence: 99%
“…The approach provides a basis for undertaking increased cultivation of black cohosh from seed on a year round basis. The approach described for generating young tissues from germinated seedlings has been instrumental in developing a transformation system and plant cell cultures for the application of modern functional genomics approaches to the study of biosynthesis of bioactive secondary metabolites in black cohosh [21].…”
Section: Introductionmentioning
confidence: 99%
“…A candidate gene encoding an unspecified amine oxidase has been identified by Spiering et al [53]. N -Guanidinopyrroline may through yet to be identified steps be converted into cimipronidine.…”
Section: 4 Guanidino Alkaloidsmentioning
confidence: 99%
“…Another critical molecule in the biosynthetic pathways of isoquinoline alkaloids is reticuline ( 27 ), which was identified at level 1 by comparison with authentic standard. The study by Spiering et al identified a candidate gene for N -methylcoclaurine 3-hydroxylase, an enzyme involved in the biosynthesis of reticuline, providing a mechanistic basis for the origin of this group of alkaloids in black cohosh [53]. …”
Section: 5 Isoquinoline Alkaloidsmentioning
confidence: 99%